A loucura está na rua: práticas e definições sobre a loucura em Caicó-RN (1926-1960) - Almeida, Sérgio Medeiros de (2022)
This research aims to carry out an analysis of the definitions and practices of madness in the hinterlands of Caicó, Rio Grande do Norte, in the mid-twentieth century. The analysis will start from the case study of Mr. Cícero Leandro da Silva, to understand the construction of definitions about madness and madness by medical knowledge and also by society, especially the wealthier classes. More specifically, this research covers the period between 1926 - year of the foundation of Hospital do Seridó, the first hospital in the Seridó region - and 1960 - year of Cícero's death. This period represents a time of significant changes in behavior, politics and economy, not only in Brazil, but in the western world. Regarding the sources that we will use to carry out this research, there are: the Police Inquiry into the Death of Cícero, the Medical Record of the Hospital de Alienados do Rio Grande do Norte (1947), the Writ of Mandamus (1943) and also the which after his death was written in the newspaper A Folha, as well as in the books of chroniclers and memorialists in the Seridó region. We will also make use of dictionaries of the Portuguese language from the 18th and 19th century, the dictionaries of the Catholic priest D. Rafael Bluteau, from 1728 and 1789, and of Luiz Maria da Silva Pinto, from 1832, to understand how the multiplicity of entries took place and the indefiniteness of madness. And from the Dictionary of Popular Medicine by Pedro Luiz Napoleão Chernoviz, “for use by families”: the ways of dealing with the madman are indicated, from 1890. the existence of “others” Ciceros, through anecdotes and stories, which remained lived in local memory, but which also, for the time being, many times these same individuals were excluded or suffered violence in that society, which still treated the other, the different, the deviant, as that being that should be removed from the spaces of social coexistence, and in extreme cases be arrested or admitted to hospitals.